Chemical exchange rotation transfer (CERT) on human brain at 3 Tesla. Issue 6 (25th May 2018) - Lin, Eugene C.; Li, Hua; Zu, Zhongliang; Louie, Elizabeth A.; Lankford, Christopher L.; Dortch, Richard D.; Does, Mark D.; Gore, John C.; Gochberg, Daniel F.
Abstract : Purpose: To test the ability of a novel pulse sequence applied in vivo at 3 Tesla to separate the contributions to the water signal from amide proton transfer (APT) and relayed nuclear Overhauser enhancement (rNOE) from background direct water saturation and semisolid magnetization transfer (MT). The lack of such signal source isolation has confounded conventional chemical exchange saturation transfer (CEST) imaging. Methods: We quantified APT and rNOE signals using a chemical exchange rotation transfer (CERT) metric, MTRdouble . A range of duty cycles and average irradiation powers were applied, and results were compared with conventional CEST analyses using asymmetry (MTRasym ) and extrapolated magnetization transfer (EMR). Results: Our results indicate that MTRdouble is more specific than MTRasym and, because it requires as few as 3 data points, is more rapid than methods requiring a complete Z‐spectrum, such as EMR. In white matter, APT (1.5 ± 0.5%) and rNOE (2.1 ± 0.7%) were quantified by using MTRdouble with a 30% duty cycle and a 0.5‐µT average power. In addition, our results suggest that MTRdouble is insensitive to B0 inhomogeneity, further magnifying its speed advantage over CEST metrics that require a separate B0 measurement. However, MTRdouble still has nontrivial sensitivity to B1 inhomogeneities. Conclusion: We demonstrated that MTRdouble is an alternative metric to evaluate APT and rNOE, which is fast, robust to B0 inhomogeneity, and easy to process.